Journal of ethics & entrepreneurship (Godbold School of Business, Gardner-Webb University, 2011)
"The mission of JEE is to publish (double-blind, peer-reviewed) interdisciplinary scholarly research (conceptual, theoretical, empirical) or teaching cases that connect entrepreneurship and ethics and appeal to both the academic and the practitioner."